228 Idiopathic Intracranial Hypertension and Pregnancy: A Comprehensive Review of Management. (19th August 2022) - Scott, C; Kaliaperumal, C
Abstract: Aim: To investigate idiopathic intracranial hypertension (IIH) and its management during pregnancy. Method: PubMed and Embase databases were searched for studies on pregnancy and IIH, with the most recent search in July 2021. Mesh terms used were "idiopathic intracranial hypertension" or "pseudotumor cerebri" AND "pregnancy". Papers were limited to studies with human subjects and written in the English language. There were no restrictions in study design or date of publication. The reference lists of all retrieved articles were reviewed for further identification of potentially relevant publications. Results: Management of IIH during pregnancy is similar to those who are non-pregnant. It is recommended that pregnant women with IIH are treated in health care settings that have access to multi-specialty input. Management depends on disease severity and includes conservative management, the use of medication such as steroids and diuretics, lumbar punctures, and surgical management. An indication for surgical management includes worsening visual deterioration despite initial management with medication or serial lumbar punctures. Surgical management includes cerebral spinal fluid diversion procedures and optic nerve sheath fenestration. These operations can be performed in all three trimesters of pregnancy. IIH in pregnancy does not increase morbidity or mortality in the newborn and method of delivery should be based on obstetrical indication. Conclusion: This review highlights the role of multi-disciplinary approach in the management of IIH during pregnancy.